The Species Composition and Structure of Vegetation in Karst Area Gunung Cibodas, Ciampea, Bogor - Peni Widiyanti; Cecep Kusmana (Jurnal Silvikultur Tropika, 2014)
Karst area is carbonated rock area that showing karst morphology, with high valued ecosystem of flora and fauna. One of the karst areas in West Java that has quite alarming condition is Gunung Cibodas, Ciampea subdistrict, Bogor regency. The research was aimed to analyze the spesies composition and structure of vegetation in the karst area of Gunung Cibodas. Sampling plot was set up using systematic sampling with random start method. Vegetation plots were laid on each slope and the mouth of cave.Our obtained results showed that 30 species of seedling, 32 species of sapling, 2 species of pole, 6 species of tree and 92 species of understorey in the karst of Gunung Cibodas, Ciampea, Bogor.On every hill slope and the mouth of cave is dominated by pioneer species such as Leucaena leucocephala, Calliandra calothyrsus and Macaranga peltata which show the process of secondary succession,moreover the understorey is dominated by the species of Invasive Alien Species (IAS). Stand structure showing inverted J-shaped curve is only found on the northern slopes. Generally canopy stratification in this karst area consists of three strata, namely stratum C, D and E with the clumping distribution pattern for dominant tree species at both mouth the cave and the slopes of mountain.